Improving Shopping Experience: Goods Economic Information System Using Content-Based Filtering Algorithm - Rahayu, Febriya Sri; Tay, En; Puspowati, Rr Isni Anisah; S, Miranti Andhita (Informatics Management, Engineering and Information System Journal, 2024)
The owner's income drop in a sports equipment firm stems from insufficient consumer interest in the physical store of a particular sports equipment company, attributed to unattractive product displays and a difficult-to-access location. This study presents a product recommendation system based on searches for items analogous to the desired sports, which can significantly enhance the owner's revenue and streamline the purchasing experience for consumers without necessitating a visit to a physical store. The study utilizes a descriptive methodology for data acquisition, encompassing observation, interviews, and literature reviews. The employed system development methodology is Rapid Application Development (RAD), while the approach utilized is Content-Based Filtering (CBF). Implementing the CBF approach in the product recommendation information system can facilitate consumers' selection of necessary things without visiting a physical store, consequently enhancing the owner's revenue at the specific sports equipment company. This research indicates that improving the shopping experience via technology can reconcile online and physical retail, resulting in increased consumer happiness and loyalty and sustainable company growth for the owner.